RESPONSE OF MAIZE YIELD AND YIELD COMPONENTS TO TILLAGE SYSTEM AND PLANT POPULATIONS - & Al- Ubaidi, Al-Rubaie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field study was conducted at the experimental farm, College of Agriculture, Abu-Ghraib (Alternative site), Baghdad , Iraq, during the spring and fall seasons of 2017, to evaluate the effects of tillage systems (zero tillage T1, Surface tillage T2, normal tillage T3) and three plant populations ( 66666 D1, 57143 D2, 50000 D3) on yield and it’s Components of two maize (Zea mays L.) cultivars (Maha V1 and Fajr V2). The layout of the experiment was split split plot design with three replications, Results were revealed that the zero tillage (T1) was superior to surface and normal tillage in weight of 300 grains both seasons spring and fall. Also the same treatment was the best in ears number plant-1, plant height and grains yield (6.92) ton.ha-1 . the increase in plant density leds to increase in leaf area, weight of 300 grains and grains yield 4.97 ton.ha-1 wich obtained from (D1).while The treatment of (D2) was superior in plant height in spring and fall seasons. Cultivar Maha (V1) was superior to cultivar Fajr 1 (V2) in some chracters, including plant height and the leaf area, the weight of 300 grains and grains yield, (6.70 ton.ha-1). Also the interaction treatments varied among them, the interaction (D2 × T1) gave the highest plant height reached 148.53 cm in fall season, Different mazie traits were differed due to different types of interaction